Samaritanos e Judaítas, entre compartilhamentos e rivalidades durante os períodos persa e helenístico: uma herança negada - Silva, Omar João da (2023)
The outline of this research and, therefore, its delimitation, takes place from the theme "the relationship between samaritans and judaites between the VI-II centuries BC". To this examination is grouped and explored by studies of biblical and extra-biblical literary, archaeological, royal, iconographic, numismatic, epigraphic, paleographical evidence, among others. Reflecting the findings of these analyses, it is possible to question some widely disseminated positions that guide much of the academic research on the origin and history of the samaritans and their relationship with the Judaites. It is concluded, therefore, that the term samaritan has a close relationship with the history of Samaria, the capital of the ancient kingdom of Northern Israel, and that it is a designation attributed by the Assyrians to the entire northern Israelite population when they conquered the ancient kingdom of Israel. North, in 722/20 BC. It also follows that the end of the ancient kingdom of Northern Israel is not the end of its population. Evidence confirms that most of the North Israelite population remained in the land and that Samaria was not destroyed. With this, the thesis reaffirms the population continuity of the North and the preservation of its material and religious culture. Another conclusion is that there was an intense relationship of sharing and mutual sharing, at different levels, between northern yahwists and southern yahwists until the end of the second century BC, when the first, incisive and profound estrangement between both communities occurred. The process of estrangement and subsequent segregation between judaites and samaritans began when the Hasmoneans, one of the resistance groups opposed to Hellenic culture and its way of organizing and thinking about society, takes over the government in Judah and has as ideological policy the reforms of Hezekiah and Josiah. The Hasmoneans had no royal or priestly lineage and, in order to establish themselves in power, they implanted a culture of exclusion, denial and differentiation. To this end, they make use of literary and discursive narratives, in order to consolidate a “culture of rivalries and resentments”, legitimized by textual productions, insertions, adjustments and resignifications such as Esd/Ne, 1 and 2Cr, 2Ks 17.24, Gn 34, 37 -38, among others. The result, therefore, is the creation of a cycle of violence, alienation, separations, exclusions, stereotypes, divisions and denials, with the aim of establishing identities. We carried out this research, mainly through a bibliographic survey of works published abroad, which inform the current stage of research on the Samaritans and their relationship with the Judaites, both from the point of view of biblical literature and archaeological evidence. Thus, it is concluded that the narrative about a split and rupture between samaritans and judaites dated to the eighth century BC, serves the interests of denying the samaritan heritage in the reconstruction and social, cultural and religious reorganization of Judah, after its collapse to the Babylonians.(AU)